Mn-doped ZnO thin films as a platform for reagentless uric acid biosensor - Bilasini Devi Naorem; Jatinder Pal Singh; Babita Sharma; Satyam Garg; Athira C; Hashima Sherin; Mahima Momaliya; Muskan; Shubhi Sahu; Arijit Chowdhuri; Mallika Verma; Monika Tomar; et al. (Chemical Physics Impact)
In this study, sol gel technique is used to fabricate manganese (Mn) doped ZnO thin films and further utilize them as a platform for uric acid biosensors. The objective was to introduce manganese into the ZnO matrix to enhance its redox properties, capitalizing on the multivalent nature of manganese. The Mn-doped thin films of concentrations varying from 3 %,5 %,7 % and 10 % were prepared and further characterized using UV–vis spectroscopy, X-ray diffraction (XRD) spectroscopy, Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM) and cyclic voltammetry (CV) measurements. The ZnO thin films with 7 % doping of Mn exhibited improved redox behaviour, as evident by the distinct redox peaks. In order to immobilise the uricase enzyme, the 7 % Mn doped composition was used, creating a highly sensitive and focused uric acid detection platform. The fabricated biosensor exhibits excellent performance in terms of sensitivity (40 µAmM-1cm-2), selectivity with <5 % deviation found in presence of other known markers present in human sera, and shelf life >12 weeks, enabling precise and sensitive uric acid detection. This study brings to light an alternate approach in developing point of care biosensors using transition metal doped ZnO thin films.